Active defects in MOS devices on 4H-SiC: A critical review. (May 2016) - Amini Moghadam, Hamid; Dimitrijev, Sima; Han, Jisheng; Haasmann, Daniel
Abstract: The state-of-the-art 4H-SiC MOSFETs still suffer from performance (low channel-carrier mobility and high threshold voltage) and reliability (threshold voltage instability) issues. These issues have been attributed to a large density of electrically active defects that exist in the SiO2 –SiC interfacial region. This paper reviews the earlier and the latest results about the responsible defects for the performance and reliability issues of SiC MOS devices, in the context of the evolution of physical understanding of these defects. The aim of this critical review is to clarify possible confusions due to inconsistencies between the earlier and the latest results. Specific clarifications relate to the physical position of the active defects (whether they are located at or near the SiO2 –SiC interface) and the energy position of their energy levels (above or below the bottom of conduction band).